An in-depth investigation of the causes of persistent low membership of community-based health insurance: a case study of the mutual health organisation of Dar Naïm, Mauritania - Maria-Pia Waelkens; Yves Coppieters; Samia Laokri; Bart Criel (BMC, 2017)
Abstract Background Persistent low membership is observed in many community-based health insurance (CBHI) schemes in Africa. Causes for low membership have been identified and solutions suggested, but this did not result in increased membership. In this case study of the mutual health organisation of Dar Naïm in Mauritania we explore the underlying drivers that may explain why membership continued to stagnate although several plans for change had been designed. Methods We used a systems approach focussed on processes, underlying dynamics and complex interactions that produce the outcomes, to delve into 10 years of data collected between 2003 and 2012. We used qualitative research methods to analyse the data and interpret patterns. Results Direct causes of stagnation and possible solutions had been identified in the early years of operations, but most of the possible solutions were not implemented. A combination of reasons explains why consecutive action plans were not put into practice, showing the complexity of implementation and the considerable management capacity required, as well as the challenges of integrating a novel organisational structure into exiting social structures. Conclusions For any CBHI project aiming at high membership, skilled professional management seems essential, with capacity to question and adapt routine procedures and interpret interactions within the wider society. Countries that include community-based health insurance in their strategic plan towards universal coverage will have to pay more attention to management capacity and the minutiae of implementation.